Inflammatory Markers Mediate the Association Between Cardiovascular Health and Chronic Inflammatory Airway Diseases: A Cross-Sectional Study on the Population Aged 50 Years and Above From NHANES 2013–2018 - Zhaoqi Yan; Xiufan Du; Jing Zhang (Mediators of Inflammation)
Conclusion: Moderate and low levels of CVH pose a threat for developing CIAD, with inflammatory factors playing a major mediating role in this association.